2004
DOI: 10.1016/j.carbon.2003.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of organic molecules from aqueous solutions on carbon materials

Abstract: Adsorption of organic molecules from dilute aqueous solutions on carbon materials is a complex interplay between non-electrostatic and electrostatic interactions. Non-electrostatic interactions are essentially due to dispersion and hydrophobic interactions, whereas the electrostatic or coulombic interactions appear with electrolytes when they are ionized at the experimental conditions used. Both interactions depend on the characteristics of the adsorbent and the adsorptive and the solution chemistry. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
597
1
27

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,216 publications
(671 citation statements)
references
References 23 publications
21
597
1
27
Order By: Relevance
“…Such adsorption implies that oxidation of the carbon surface should promote adsorption capacity. However, several works report a decrease in phenol adsorption from water with surface oxidation Mahajan et al, 1980;Leng, 1996;Franz et al, 2000;Terzyk, 2003Terzyk, , 2004Moreno-Castilla, 2004). Since lignites are rich in oxygen surface groups Küçükbayrak et al, 2000), they have a high affinity for water (Allardice and Evans, 1971;Schafer, 1972;Kaji et al, 1986;Müller and Gubbins, 1998;Lee and Reucroft, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Such adsorption implies that oxidation of the carbon surface should promote adsorption capacity. However, several works report a decrease in phenol adsorption from water with surface oxidation Mahajan et al, 1980;Leng, 1996;Franz et al, 2000;Terzyk, 2003Terzyk, , 2004Moreno-Castilla, 2004). Since lignites are rich in oxygen surface groups Küçükbayrak et al, 2000), they have a high affinity for water (Allardice and Evans, 1971;Schafer, 1972;Kaji et al, 1986;Müller and Gubbins, 1998;Lee and Reucroft, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely the adsorption of cations by the biomaterials due to charge difference between the metal ion and the surface. 23,24 The isotherm of adsorption of N 2 (g), at 77K, is a combination of type II and type III according to the classification of Brunauer, with a greater contribution of the last one, which indicates a nonporous biosorbent. 25 Additionally, it was observed that 51.7% of the S BET can be attributed to external surface.…”
Section: Crab Shell Characterizationmentioning
confidence: 99%
“…Hence, we may easily observe (see Online Resource) that adsorption of SA was always the strongest (the same adsorption as for BA was obtained at 2-3 times lower equilibrium concentrations) and adsorption of phenol of 50 % of SA and 65 % of BA adsorption for the same solute concentration. Explanation of this behavior is mainly the Traube's rule-the main factor affecting adsorption for similar adsorbates in the same molecular state (all adsorbates are mostly in molecular form at pH = 2) are their relative concentrations c/c s , where c s is saturation concentration (see Table 3) (DeryloMarczewska and Jaroniec 1987;Derylo-Marczewska and Marczewski 1999;Moreno-Castilla 2004). Salicylic acid has the lowest solubility (half of BA solubility), whereas solubility of phenol has solubility larger by more than 1 order of magnitude and their adsorption properties may be ordered as follows: SA [ BA [ Ph.…”
Section: Adsorption From Solution-equilibrium Isothermsmentioning
confidence: 99%
“…Salicylic acid has the lowest solubility (half of BA solubility), whereas solubility of phenol has solubility larger by more than 1 order of magnitude and their adsorption properties may be ordered as follows: SA [ BA [ Ph. Moreover, intramolecular hydrogen bond formation in SA (hydroxyl and carboxyl groups in ortho position) resulting in weaker solvation effects may also be responsible for its lower solubility in water and stronger affinity to graphene-like structures in carbons (Moreno-Castilla 2004). Partial evidence of this effect may also be seen in molar volumes (as calculated from solid density data) showing that the SA molecule occupies even less space than BA, despite having an additional hydroxyl group (Table 3).…”
Section: Adsorption From Solution-equilibrium Isothermsmentioning
confidence: 99%
See 1 more Smart Citation